Regulation of adhesion and growth of fibrosarcoma cells by NF-kappa B RelA involves transforming growth factor beta. - Perez, J R (1994)
The NF-kappa B transcription factor is a pleiotropic activator that participates in the induction of a wide variety of cellular genes. Antisense oligomer inhibition of the RelA subunit of NF-kappa B results in a block of cellular adhesion and inhibition of tumor cell growth. Investigation of the molecular basis for these effects showed that in vitro inhibition of the growth of transformed fibroblasts by relA antisense oligonucleotides can be reversed by the parental-cell-conditioned medium. Cytokine profile analysis of these cells treated with relA antisense oligonucleotides revealed inhibition of transforming growth factor beta 1 (TGF-beta 1 to the transformed fibroblasts reversed the inhibitory effects of relA antisense oligomers on soft agar colony formation and cell adhesion to the substratum. Direct inhibition of TGF-beta 1 expression by antisense phosphorothioates to TGF-beta 1 mimicked the in vitro effects of blocking cell adhesion that are elicited by antisense relA oligomers. These results may explain the in vitro effects of relA antisense oligomers on fibrosarcoma cell growth and adhesion.